Análise morfofuncional da via aérea superior durante exercícios orofaríngeos para reabilitação dos distúrbios respiratórios do sono - Silva, Andresa Santos da (2020)
INTRODUCTION: the speech therapy approach through Orofacial Myofunctional Therapy (BMT) has been presented as one of the possibilities of alternative treatment for sleep obstructive respiratory disorders, evidenced in studies with adults and children. Although the effectiveness of this intervention has been demonstrated, the morpho functional mechanisms that trigger the results obtained are poorly elucidated. OBJECTIVE: perform morpho-functional analysis of the Upper Airway during oropharyngeal exercises seeking to verify its immediate effects on mobility, stiffening and modification of oropharyngolaryngeal spaces, as well as, to verify which exercises provide greater changes in Upper Airway and greater electrical activity in suprahyoid muscles and masseters. METHOD: from the specific literature, thirteen exercises were selected for analysis. After relevant ethical processes ( CAAE: 94754418.4.0000.5482 ), respecting inclusion and exclusion criteria, fifteen healthy adult subjects, both sexes, with a mean age of 27.5 years, underwent clinical orofacial myofunctional evaluation and individual training on how to perform each exercise. Data collection consisted of surface electromyographic assessment (EMGs) of the masseter and suprahyoid muscles and recording of Upper Airway dynamics through Nasofibrolaryngoscopy (NFL), during the performance of each exercise. For the EMGs analysis, the data were normalized, tabulated according to the average of the potentials obtained and submitted to statistical analysis: ANOVA, Mauchly's test with Greenhouse correction - Geisser, tests Least Significant Difference (LSD), Bonferroni, and Pearson for correlation of results between the pairs of muscles analyzed. As for the NFL data, the exercises were recorded in two regions: nasopharynx and oropharynx / hypopharynx resulting in a sample of 390 videos, sent to the judges: three otorhinolaryngologists, blind to the subjects and to the exercises. The analyzes were recorded in a specific instrument consisting of structural verification , movement type and classification. It was made analysis of agreement between the judges: Fleiss Kappa Agreement Coefficient, for the comparison between exercises, the Friedman Test was used. RESULTS: The subjects presented vertical and transverse mobility of the present soft palate, extension of the normal uvula, symmetry of the present uvula, normal oropharyngeal region, medium face with straight or convex profile. The 13 exercises analyzed provide a mechanism of action in the Upper Airway and electrical activity of the suprahyoid muscles and masseters. The methodology used allowed to identify which exercises have greater electromyographic responses and which provide greater mobility, stiffness and modification for the regions of soft palate, pharyngeal / hypopharyngeal wall, retrolingual region and epiglottis. CONCLUSION: The results of the present study collaborate to comprehension how the exercises used in orofacial myofunctional therapy for OSA act and contribute to choosing the best clinical approach in other areas of speech therapy